2011
DOI: 10.1016/j.pecs.2010.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in the development of diesel surrogate fuels

Abstract: There has been much recent progress in the area of surrogate fuels for diesel. In the last few years, experiments and modeling have been performed on higher molecular weight components of relevance to diesel fuel such as n-hexadecane (n-cetane) and 2,2,4,4,6,8,8-heptamethylnonane (iso-cetane). Chemical kinetic models have been developed for all the n-alkanes up to 16 carbon atoms. Also, there has been much experimental and modeling work on lower molecular weight surrogate components such as n-decane and n-dod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
371
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 636 publications
(378 citation statements)
references
References 188 publications
1
371
0
1
Order By: Relevance
“…evaporation) of the target fuel must be considered in its development, depending on the target property or application [8]. Primary reference fuel (PRF) is a commonly used surrogate for gasoline and is a mixture of iso-octane and n-heptane.…”
Section: Surrogate Formulationmentioning
confidence: 99%
“…evaporation) of the target fuel must be considered in its development, depending on the target property or application [8]. Primary reference fuel (PRF) is a commonly used surrogate for gasoline and is a mixture of iso-octane and n-heptane.…”
Section: Surrogate Formulationmentioning
confidence: 99%
“…Schofield [1] states that these large scale models are adequate as engineering tools for studying the combustion of new fuel molecules. A recent review paper by Pitz and Mueller [2] describing the development of diesel surrogate fuel models concluded that major research gaps remain in modeling high molecular weight (i.e., C 8 and greater) aromatics, alkyl aromatics, cyclo-alkanes, and lightly branched iso-alkanes. The present study is concerned with the combustion of branched alkanes, specifically 2,5-dimethylhexane, which has been reported as a component of petroleum combustion exhaust, smog, and tobacco smoke [3].…”
Section: Introductionmentioning
confidence: 99%
“…The present study is concerned with the combustion of branched alkanes, specifically 2,5-dimethylhexane, which has been reported as a component of petroleum combustion exhaust, smog, and tobacco smoke [3]. Branched alkanes are important components of conventional diesel and jet fuels derived from petroleum [2,4]; synthetic Fischer-Tropsch diesel and jet fuels derived from coal, natural gas, and/or biomass [5,6]; and renewable diesel and jet fuels derived from thermochemical treatment of bio-derived fats and oils (e.g., hydrotreated renewable jet (HRJ) fuels) [7,8]. Detailed compositional reports by Bruno and coworkers [8,9] for turbine fuels, such as GTL, CTL, SPK, and biomass-derived fuels indicate that di-methylated alkanes represent an important fraction of the fuel composition.…”
mentioning
confidence: 99%
“…Although there is a substantial progress made in understanding and in development of sophisticated model reduction approaches, in applications, the mostly used methodology is still based on the concept of skeletal mechanisms [4]. This is due to the simplicity of implementation and the intuitive nature of such an approach.…”
Section: Introductionmentioning
confidence: 99%